Comparison between the Express Implant and Transscleral Diode Laser in Neovascular Glaucoma - Faried Mohammed Wagdy; Adel Galal Zaky (Journal of Ophthalmology)
Purpose. To compare the outcomes of Ex-PRESS glaucoma filtration device and transscleral cyclophotocoagulation (TSCP) in the management of neovascular glaucoma (NVG). Patients and Methods. A total of 30 eyes (12 express shunts and 18 TSCP) of 28 patients were included. The eyes had NVG with intraocular pressure (IOP) more than 21 mmHg of the maximally tolerated medication treatment after previous panretinal photocoagulation and antivascular endothelial growth factor (anti-VEGF) injection, with no previous history of a cyclodestruction procedure or glaucoma surgery, were randomized either for Ex-PRESS glaucoma filtration device or TSCP. The patients were followed up weekly for the first month and then monthly for 12 months as regard to the IOP, number of topical antiglaucoma drugs required, visual outcome, and postoperative complications. Results. IOP was successfully controlled with both techniques in 83.3% of the eyes. Both techniques had fewer complications and required fewer subsequent procedures. Conclusion. Both the Ex-PRESS glaucoma filtration device and TSCP might constitute safe and alternative therapeutic tools for patients with NVG. However, TSCP is an easier procedure, less time consuming, and does not require a learning curve.